A Mechanism for Genome Size Reduction Following Genomic Rearrangements - Ren, Longhui; Huang, Wei; Cannon, Ethalinda K. S.; Bertioli, David J.; Cannon, Steven B. (Frontiers in Genetics, 2018)
The factors behind genome size evolution have been of great interest, considering that eukaryotic genomes vary in size by more than three orders of magnitude. Using a model of two wild peanut relatives, Arachis duranensis and Arachis ipaensis, in which one genome experienced large rearrangements, we find that the main determinant in genome size reduction is a set of inversions that occurred in A. duranensis, and subsequent net sequence removal in the inverted regions. We observe a general pattern in which sequence is lost more rapidly at newly distal (telomeric) regions than it is gained at newly proximal (pericentromeric) regions – resulting in net sequence loss in the inverted regions. The major driver of this process is recombination, determined by the chromosomal location. Any type of genomic rearrangement that exposes proximal regions to higher recombination rates can cause genome size reduction by this mechanism. In comparisons between A. duranensis and A. ipaensis, we find that the inversions all occurred in A. duranensis. Sequence loss in those regions was primarily due to removal of transposable elements. Illegitimate recombination is likely the major mechanism responsible for the sequence removal, rather than unequal intrastrand recombination. We also measure the relative rate of genome size reduction in these two Arachis diploids. We also test our model in other plant species and find that it applies in all cases examined, suggesting our model is widely applicable.